Pharmacologically induced N‐methyl‐D‐aspartate receptor hypofunction impairs goal‐directed food seeking in rats - Takaaki Ozawa; Tatsumi Itokazu; Yukio Ichitani; Kazuo Yamada (Wiley, 2021)
Abstract Aim Acute N‐methyl‐D‐aspartate (NMDA) receptor antagonism is an important pharmacological animal model of schizophrenia. In previous studies, schizophrenia patients show impaired goal‐directed behavior in an outcome‐specific devaluation procedure. In this study, we investigated whether the rat model of the NMDA receptor blockade also showed altered goal‐directed behavior in a satiety‐induced outcome devaluation paradigm. Methods In experiments 1 and 2, we aimed to establish the satiety‐induced outcome devaluation test using sucrose and lipid rewards in operant conditioning and free consumption paradigms. In experiment 3, we tested the effect of MK‐801 (0.1 mg/kg, i.p.) on outcome‐specific devaluation. Results Experiments 1 and 2 demonstrated that 1‐h ad libitum food consumption is sufficient to induce outcome‐specific devaluation in both lever‐press and free consumption tests in rats. Experiment 3 showed that the administration of MK‐801 impaired satiety‐induced devaluation in the lever‐press test but not in the subsequent free consumption test. Conclusions Our results suggest that acute pharmacological NMDA receptor antagonism in rats is a useful animal model for impaired goal‐directed behavior in schizophrenia.